1999
DOI: 10.1097/00000374-199911000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Directly Excites Dopaminergic Ventral Tegmental Area Reward Neurons

Abstract: These data provide strong evidence that ethanol directly excites dopaminergic VTA neurons, as this excitation still occurs in the absence of input from surrounding neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
143
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 3 publications
12
143
0
Order By: Relevance
“…However, other drugs of abuse, such as alcohol, cannabinoids or opiates, have been shown to decrease cell activity following withdrawal from their repeated administration (Diana et al 1993(Diana et al , 1995Bailey et al 2001). Interestingly, whereas these other drugs acutely increase dopamine cell activity (Gysling and Wang 1983;Matthews and German 1984;Mereu et al 1984;Gessa et al 1998;Brodie et al 1999), psychostimulants decrease it (Bunney et al 1973(Bunney et al , 2001Wang 1981;Einhorn et al 1988;Lacey et al 1990). Thus, it is possible that these neuroadaptations represent a compensatory response such that repeated administration of drugs that reduce impulse activity produces rebound increase in cell activity upon discontinuation, whereas repeated administration of drugs that increase impulse activity has opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, other drugs of abuse, such as alcohol, cannabinoids or opiates, have been shown to decrease cell activity following withdrawal from their repeated administration (Diana et al 1993(Diana et al , 1995Bailey et al 2001). Interestingly, whereas these other drugs acutely increase dopamine cell activity (Gysling and Wang 1983;Matthews and German 1984;Mereu et al 1984;Gessa et al 1998;Brodie et al 1999), psychostimulants decrease it (Bunney et al 1973(Bunney et al , 2001Wang 1981;Einhorn et al 1988;Lacey et al 1990). Thus, it is possible that these neuroadaptations represent a compensatory response such that repeated administration of drugs that reduce impulse activity produces rebound increase in cell activity upon discontinuation, whereas repeated administration of drugs that increase impulse activity has opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are thought to be mediated by the mesolimbic dopaminergic pathway arising from the ventral tegmental area and projecting to the nucleus accumbens and prefrontal cortex. Ethanol was shown to increase the dopamine level after intake (Bunney et al 2000;Katner and Weiss 2001;Nurmi et al 1998;Yavich and Tiihonen 2000;Yim and Gonzales 2000;Yoshimoto et al 2000) and excites dopaminergic ventral tegmental area reward neurones directly (Brodie et al 1999). Cocaine increases dopamine levels by blocking the dopamine transporter (Ferraro et al 2000;Rocha et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The mesocorticolimbic dopaminergic system, referred to as the brain reward circuit, has suggested a strong role of dopamine (DA) in the effects of addictive drugs, including alcohol. DA has been implicated in rewarding effects, such as the subjective experience of "pleasure" (Brodie et al 1999;Hyman and Malenka 2001), in mechanisms involved in the development of dependence (Bassareo et al 1996;Giacchino and Henriksen 1996;Peters et al 2000), and in reinforcing actions of abused drugs such as alcohol (Weiss and Porrino 2002). In fact, many structures of the brain reward circuit show increases in the turnover of DA after alcohol administration (Tabakoff and Hoffman 1992;Di Chiara 1995;O'Brien et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many structures of the brain reward circuit show increases in the turnover of DA after alcohol administration (Tabakoff and Hoffman 1992;Di Chiara 1995;O'Brien et al 1995). Brodie et al (1999) suggested that the rewarding properties of alcohol seem to result from its ability to directly excite dopaminergic ventral tegmental area neurons, which results in increased DA release in the nucleus accumbens. However, there is evidence suggesting that DA might serve more as a "learning signal" than as a mediator of rewarding mechanisms (Spanagel and Weiss 1999;Hyman and Malenka 2001).…”
Section: Introductionmentioning
confidence: 99%